2020
DOI: 10.7717/peerj.10456
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution at mRNA editing sites in soft-bodied cephalopods

Abstract: Background The bulk of variability in mRNA sequence arises due to mutation—change in DNA sequence which is heritable if it occurs in the germline. However, variation in mRNA can also be achieved by post-transcriptional modification including mRNA editing, changes in mRNA nucleotide sequence that mimic the effect of mutations. Such modifications are not inherited directly; however, as the processes affecting them are encoded in the genome, they have a heritable component, and therefore can be shaped by selectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 69 publications
3
22
2
Order By: Relevance
“…Such a strong unidirectional tendency can produce guanine richness under plausible positive selection pressure. For example, a positive selective bias from adenine-to-guanine transition has recently been characterized in soft-bodied cephalopods by Moldovan et al (2020) 23 . These authors suggested that edited adenines tend to be substituted to guanines, and this tendency is supported by positive selection at highly edited sites.…”
Section: Discussionmentioning
confidence: 99%
“…Such a strong unidirectional tendency can produce guanine richness under plausible positive selection pressure. For example, a positive selective bias from adenine-to-guanine transition has recently been characterized in soft-bodied cephalopods by Moldovan et al (2020) 23 . These authors suggested that edited adenines tend to be substituted to guanines, and this tendency is supported by positive selection at highly edited sites.…”
Section: Discussionmentioning
confidence: 99%
“…Such a strong unidirectional tendency can produce guanine richness under plausible positive selection pressure. For example, a positive selective bias from adenine-to-guanine transition has recently been characterized in soft-bodied cephalopods by Moldovan et al 24 . These authors suggested that edited adenines tend to be substituted to guanines, and this tendency is supported by positive selection at highly edited sites.…”
Section: Discussionmentioning
confidence: 99%
“…Re-coding (non-synonymous) A-to-I editing in coleoids might be beneficial, as it diversifies the proteome and, consequently, allows for appropriate phenotypic and evolutionary responses to novel environments 13,14,22 . In line with this reasoning, we compared the fraction of re-coding sites among up-and downstream adenines in AA-clusters (Fig.…”
Section: Directionality Of Dense Clustersmentioning
confidence: 99%
“…Editing in coleoids, involving up to 1% of all adenines in their transcriptomes, has been suggested to play an important role in proteome diversification, allowing for complex responses to the environment demonstrated by coleoids 13,14 . Along with that, editing sites could have an evolutionary value by rescuing deleterious G-to-A substitutions 38,39 or by enhancing the heritable trait variance needed for adaptation 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation